Low-fish-meal-content feed for salmon - MIAO E (2016)
The invention relates to low-fish-meal-content feed for a salmon, and belongs to the technical field of a feed. The feed is manufactured from the following raw materials, according to a weight part ratio, 2-5 parts of fish meal, 25-40 parts of a raw vegetable protein material, 35-60 parts of a raw animal protein material, 0.4-1 part of a mineral feed, 0.7-1.2 parts of a vitamin premix feed, 8-15 parts of green feed, and 3-8 parts of a health-care reinforcement material. In the low-fish-meal-content feed, vegetable protein and animal protein are selected as the raw protein materials to reduce dependence of the salmon on fish meal. Palatability of the feed is not affected, and the mineral feed and the vitamin premix feed are added for further improving nutritional ingredients of the feed and absorption efficiency by the salmon. The health-care reinforcement material is added for further improving disease resistance and immunity of the salmon, thereby reducing cost of the salmon in an artificial feeding environm